Morphological characterization of fullerene–androsterone conjugates - Ruiz, Alberto; Suárez, Margarita; Martin, Nazario; Albericio, Fernando; Rodríguez, Hortensia (Beilstein Journal of Nanotechnology, 2014)
Here we report on the self-organization characteristics in water of two diastereomer pairs of fullerene–androsterone hybrids that have the hydrophobic C60 appendage in the A and D ring of the androsterone moiety, respectively. The morphology and particle size in aqueous solution were determined by transmission electron microscopy (TEM) and dynamic light scattering (DLS), with satisfactory agreement between both techniques. In general, these fullerene derivatives are shown to organize into spherical nano-scale structures with diameters in the ranges of 10–20 and 30–50 nm, respectively.
Keywords: androsterone; dynamic light scattering; fullerene; transmission electron microscopy